1999
DOI: 10.1016/s0008-6363(99)00118-2
|View full text |Cite
|
Sign up to set email alerts
|

Repolarizing currents in ventricular myocytes from young patients with tetralogy of Fallot

Abstract: The electrophysiological characteristics of right ventricular myocytes isolated from children with tetralogy of Fallot resemble in most cases subendocardial myocytes from adults. The most prominent difference is a fast recovery from inactivation as well as a small rate dependent reduction of Itol. The observed EADs may have clinical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…Despite the fact that hERG is the predominant channel for human cardiac repolarization and its defects cause LQTS (1,4), an absence of I Kr in ventricular myocytes isolated from human tissues has been reported by Beuckelmann et al (48). Similarly, Schaffer et al (49) reported that I Kr was absent in 32 of 34 ventricular myo-cytes isolated from human tissue. As well, Konarzewska et al (50) reported that the delayed rectifier K ϩ current (I K ) was not measurable, but inward rectifier K ϩ current I K1 and transient outward K ϩ current I to were robust in human ventricular myocytes.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the fact that hERG is the predominant channel for human cardiac repolarization and its defects cause LQTS (1,4), an absence of I Kr in ventricular myocytes isolated from human tissues has been reported by Beuckelmann et al (48). Similarly, Schaffer et al (49) reported that I Kr was absent in 32 of 34 ventricular myo-cytes isolated from human tissue. As well, Konarzewska et al (50) reported that the delayed rectifier K ϩ current (I K ) was not measurable, but inward rectifier K ϩ current I K1 and transient outward K ϩ current I to were robust in human ventricular myocytes.…”
Section: Discussionmentioning
confidence: 97%
“…Delayed rectifier K ϩ channel currents in human cardiac myocytes are reported to be of small amplitude and in some cases have not been detected (2,15,21,25,41,(45)(46), and most quantitative data have been obtained from animal and heterologous expression models. In our hiPSC-derived cardiomyocytes, the current density and activation properties for I Kr are close to values reported for human cardiac myocytes (9,20).…”
Section: Discussionmentioning
confidence: 99%
“…There are some contradictory reports, although according to the majority of the previously published papers, it was assumed that the sex, cell location, and measurement temperature do not significantly influence the electric capacitance [16, 17]. Two studies describing age-capacitance correlation were based on the biological material derived from young individuals [18, 19]. Both of them describe non-healthy children diagnosed with the tetralogy of Fallot, which is connected with right ventricular hypertrophy [20, 21].…”
Section: Methodsmentioning
confidence: 99%